A religious justification of the role of science in human reproduction (2022)
Giving birth to children is very important in many African societies, because children are portrayed as evidence of fruitfulness and blessings from God. In fact, there is a saying that children are the gains of a marriage. Amid this huge burden and societal expectations, some couples are encumbered with this weight as a result of some medical challenges in the area of procreation. Scientific advancements have offered interventions to mitigate this problem, as is evident in other human endeavors, where scientific solutions have come to the rescue through a number of reproductive technologies. Extant literature on human reproductive technology have focused largely on the procedures and ethical perspectives with scant attention paid to it from a Christian religious perspective. This study therefore, explored a religious justification of the role of science in human reproduction. This was with a view to addressing the concerns that have been raised by varying adherents of religions and schools of thought regarding the ethics of reproductive technologies. The aim of the study was to answer questions on whether reproductive technologies contravene the natural way of human reproduction and whether they tamper with the supremacy of God. The paper concludes that there is no justifiable reason for rejecting the gift of knowledge of God to humanity through science in the area of human reproduction using St. Augustine’s Concept of Knowledge that all human knowledge comes from God.